(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2023)
Introduction: As circumcision is a common paediatric operation in Bangladesh, it logically demands costeffectiveness and safety for people’s benefit. Antibiotics abuse or its irrational use is a problem in our country. This study will help other surgeons to do clean surgery without antibiotics, which will ensure cost-effectiveness and preserving natural body immunity. Objective: The study was conducted to determine the outcome of circumcision in children with or without antibiotics. Methodology: It was a quasi-experimental study done at Paediatric Surgery unit of Institute of Child and Mother Health (ICMH), Matuail, Dhaka from August 2019 to January 2020 after taking approval for this protocol from the ethical committee of ICMH. The male infants and children who attended Paediatric Surgery OPD of Institute of Child and Mother Health (ICMH) with an intention to do circumcision voluntarily for religious cause or other reasons, included in this study excluding congenital anomaly and randomly allocated in two groups. They were counseled properly and enrolled in the study with taking written informed consent. On the scheduled operation day of every Wednesday, circumcision was done after doing investigations and anesthetic check-up. One group of 30 patients received antibiotics and another group of 30 patients were without antibiotics. They were discharged on the same day as a day care surgery and advised for follow up in a follow-up schedule of 1 week, 2 weeks and 1 month. The recovery outcomes were assessed and recorded in the data sheets. Results: 02 participants (07%) among all 30 participants without antibiotics after circumcision developed postoperative wound infection like pus in the wound, rest 28 participants (93%) without antibiotics recovered uneventful with only pain management therapy and regular cleaning by warm water bathing. Another group of 30 participants with antibiotics recovered without any post- operative complications after doing circumcision. Conclusion: Antibiotics are not necessarily mandatory for circumcision wounds. Clean surgery and proper maintenance of asepsis during per-operative and postoperative period played important role in good recovery outcome, without or treatable mild postoperative complications. Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 39-43